Air Pollution and Public Health in a Megalopolis: A Case Study of Moscow - Revich, Boris Aleksandrovich; Avaliani, Simon Levanovich; Simons, Gregory John (Economy of Regions, 2016)
A rapidly growing number of megalopolises in the world leads to some substantial problems to environmental conditions of their population. One of these problems is the intensification of motor traffic, which contributes to air pollution measured as average concentrations of several air pollutants and climate change in the form of more frequent heat waves and cold spells. The present study analyzes the selected indicators of environmental health in Moscow, the largest Russian megalopolis which contributes for adoption of sound and evidence-based health risk management policies. Individual carcinogenic risks attributed to traffic emissions varied across the study area of400 km2 between 3 x 10 and 6.53 x 10 which is typical for most megalopolises in the economically developed countries. However, the carcinogenic risks in some districts may exceed the threshold of 10-3 which is regarded as unacceptable. The total population carcinogenic risk for 3.5 million people who lived in the study area with intense road traffic was 23 additional cases of malignant neoplasms per year or 1513 cases per 70 years. Additional mortality during the extreme heat episode in the summer of 2010, when forest and peat fires caused exceptionally high levels of smog in Moscow, reached 11,000 deaths. The measures to be taken by the executive authorities include informing the residents about the onset of extreme heat by means of an early warning system, and rating the relative severity of heat and air pollution according to a 4-point scale.